Associations of cannabis product source and subsequent cannabis use among adolescents. (1st April 2022) - Kelleghan, Annemarie R.; Sofis, Michael J.; Budney, Alan; Ceasar, Rachel; Leventhal, Adam M.
Abstract: Background: Cannabis is obtained from a variety retail and illicit sources, with unknown implications for youth cannabis use. This study assessed whether source of obtaining cannabis was associated with future cannabis use among adolescents. Methods: High-schoolers (N = 835) completed 3 semiannual surveys, reporting use of 7 cannabis sources (i.e., free, bought from someone, from an online dispensary, with a [valid/invalid] medical card, self-grown, or other; separate dichotomous exposure variables) at wave 1 (n = 621; M[SD] age=17.14[.40]) or wave 2 (n = 622; M[SD] age=17.51[.39]). Past-6-month (yes/no) and number of past-30-day (0−30) non-medical use of any cannabis product, combustible, edible, and vaporized cannabis, blunts, and concentrates (i.e., dabs) were reported at waves 2–3. Random-effect time-lagged repeated-measures regression was used to test longitudinal associations of youth's cannabis source (waves 1–2; time-varying exposure) with cannabis use outcomes 6 months later (waves 2–3). Results: Most youth (72.1%) received cannabis for free; 50.9% bought cannabis from someone, 15.9% used a valid medical card at a brick-and-mortar dispensary, and 3.9% grew cannabis. Buying cannabis from someone (OR=1.46, 95% CI: 1.07–1.99, p = .02) or using a valid medical card (OR=1.99, 95% CI: 1.20–3.31, p = .008) conferred greater odds of any cannabis product use 6 months later. Buying from someone predicted subsequent past-30-day use frequency (RR=1.25, 95% CI:1.05–1.48, p = .01). Some associations between particular cannabis sources and products were observed. Conclusions: Adolescents may access cannabis from several sources. Those who purchase cannabis illicitly from someone or from a brick-and-mortar dispensary using a valid medical card may be at increased risk for more persistent and frequent patterns of non-medical cannabis use. Highlights: Most youth using cannabis report receiving cannabis for free or buying from someone. Using a valid medical card to buy cannabis confers greater odds of non-medical use. Buying cannabis from someone confers greater odds of use and more frequent use.